Public resource or private sanctuary?: access patterns and narratives from the woodland of North East Derbyshire - Lisewski-Hobson, Vivyan (2019)
Set against a backdrop of a long and turbulent debate on access to the countryside, this thesis addresses gaps in knowledge on lived experience of access to woodland. The approach is geographically situated in ordinary wooded landscapes in North East Derbyshire and uses an approach which analyses physical evidence, archives, observation and interview narratives from a range of stakeholders.